The Effectiveness of Cognitive Conflict Strategy in Comprehending Reading Among the Fifth Literary Students in the Subject of Literature and Texts (Journal Of Educational and Psychological Researches, 2022)
The aim of the current study is to identify the effectiveness of cognitive conflict strategy in comprehending reading among literary fifth students in literature and literature texts. The researcher uses experimental method with partial control. The sample consisted of (80) students distributed into control and experimental groups. The scientific material, the behavioral goals, the teaching plans, and the instrument of the research have been prepared (reading comprehension test) by the researcher.The instrument's validity and reliability have been calculated and then applied to the sample. After treating the data statistically by using SPSS, the results have revealed that there is a statistically significant difference at the significance level (0.05) between the average scores of the experimental group students and the average scores of the control group students in the reading comprehension test for the benefit of the experimental group.